2011
DOI: 10.1111/j.1530-9290.2011.00368.x
|View full text |Cite
|
Sign up to set email alerts
|

Mineral Carbonation as the Core of an Industrial Symbiosis for Energy‐Intensive Minerals Conversion

Abstract: Summary The longer term sustainability of the minerals sector may hinge, in large part, on finding innovative solutions to the challenges of energy intensity and carbon dioxide (CO2) management. This article outlines the need for large‐scale “carbon solutions” that might be shared by several colocated energy‐intensive and carbon‐intensive industries. In particular, it explores the potential for situating a mineral carbonation plant as a carbon sink at the heart of a minerals and energy complex to form an indus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
21
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(23 citation statements)
references
References 18 publications
0
21
0
Order By: Relevance
“…Such a development is very much in line with the key ideas of industrial ecology and industrial symbiosis, meaning that it appears highly relevant for the cement industry to move further in this direction, as illustrated in Figure 7, being an important actor or even an anchor tenant in industrial symbiosis networks. Brent et al (2012) provide interesting input on a more radical development, where the need for large-scale "carbon solutions" could induce new or developed symbiosis options for the cement industry, where the most energy-intensive and carbon-intensive industries could be co-located. When discussing clinker substitution it is essential to acknowledge that it affects the characteristics of the cement.…”
Section: Concluding Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Such a development is very much in line with the key ideas of industrial ecology and industrial symbiosis, meaning that it appears highly relevant for the cement industry to move further in this direction, as illustrated in Figure 7, being an important actor or even an anchor tenant in industrial symbiosis networks. Brent et al (2012) provide interesting input on a more radical development, where the need for large-scale "carbon solutions" could induce new or developed symbiosis options for the cement industry, where the most energy-intensive and carbon-intensive industries could be co-located. When discussing clinker substitution it is essential to acknowledge that it affects the characteristics of the cement.…”
Section: Concluding Discussionmentioning
confidence: 99%
“…Such articles provide information about existing or possible synergies and show that the cement industry can serve as an anchor tenant in industrial symbiosis networks (cf. Brent et al, 2012). A large part of the general industrial symbiosis literature has emphasized exchange of resources such as byproducts/wastes and energy across industries in geographical proximity (Chertow, 2000).…”
Section: -100%mentioning
confidence: 99%
“…For example, recent studies, such as those by Krevor and Lackner (2011) and Baldyga et al (2010), have identified weak acids that enhance the dissolution of natural silicate minerals and could potentially improve reaction rates. Brent et al (2011) propose the integration of mineral carbonation with power generation and other extraction/manufacturing processes involving magnesium silicates, such as the extraction of magnetite, nickel, and chromium from serpentine. This type of synergistic approach offers the potential to offset the energy penalty and costs associated with mineral carbonation using naturally occurring minerals.…”
Section: Naturally Occurring Mineral Pathwaymentioning
confidence: 99%
“…With regard to abiotic materials, Brent and colleagues () have called for large‐scale “carbon solutions” that include colocated industries. They recognize that an efficient solution requires a proximate location of sources and sink.…”
Section: Drilling Deepermentioning
confidence: 99%
“…This may comprise the design of new processes to mitigate environmental harm, for example, the sequestration of carbon dioxide (CO 2 ) (Brent et al. ). The different sources and sinks are linked through networks of actors that could be spatially analyzed explicitly in order to close loops (Lyons et al.…”
Section: Introductionmentioning
confidence: 99%